Remarks at the G20 Finance Ministers and Central Bank Governors Meeting Held during the 2021 Annual Meetings - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass discussed the Bank’s new International Debt Statistics (IDS) report, published on Monday, showing the debt of low-income countries is 860 billion U.S. dollars, up 12 percent. Turning to vaccines, developing countries need 5 billion more doses to vaccinate 70 percent of their population by the middle of next year. Some urgent steps are needed: (i) swapping near-term vaccine delivery schedules with COVAX and AVAT; (ii) closing the gap between pledges and deliveries; and (iii) eliminating trade and regulatory barriers. Finance and health ministers in developing countries should also seek contracts that include early delivery schedules.